ASSESSMENT OF QUALITY OF LIFE AND DEPRESSION IN POST BURN PATIENTS IN BURN AND PLASTIC SURGERY CENTER HAYATABAD (The Research of Medical Science Review, 2025)
Background: Burns are injuries that can affect anyone, anywhere, at any time. Burn is a severe public health issue that have a significant impact on both society and the healthcare the aim of our study is to assess the quality of life and depression in post burn patients. Objectives: The objectives of the study were to Evaluate Quality of Life and depression in Post-Burn Patients Methodology: A cross-sectional descriptive study was carried out in Tertiary care hospitals of Peshawar. A total of 282 burn injuries participants were enrolled in this study. The sample size was calculated through raosoft online software with a confidence level of 95% and a margin of error of 5%. Data were collected from those burn patients who gave written or verbal permission and met our inclusion criteria through non-probability convenient sampling method using assessment tools PHQ-9 for depression and EQ5D3L for quality of life Result: The study included 282 participants, out of which 168 were males (59.6%) and 114 were females (40.4%). The participants had an average age of 33 years, ranging from 18 to 50 years. The majority of the participants (41.5%) fall within the range of 31 to 45 years. Male were the predominant gender (59.6%) of the sample. The most frequent causes of burn were Flame burns, accounted 57.1% followed by electrical burn (15.2%), Scald burn (12.1%), chemical burn 28 (9.9%) and Thermal burn 16 (5.7%). Quality of life were impaired more in males. Most of the participants with burns injuries experience major problems in usual activities followed by problem in self-care. Depression was statistically found very common in burn patients. Males were predominant in depression. A significant difference was observed among the groups according to PHQ-9 grading of depression. 17.0% cases were in minimal depression, 18.8% in mild, 20.2% in moderate, 15.6% in moderately severe and 28.4% were severe depressed. Conclusion: It is concluded that the findings of the present study indicate that burn injuries have a negative impact on several dimensions of EQ-5D (QoL). Various risk factors including age, gender, occupational status, anatomical location, etiology, depth and percentage of Total Body Surface Area (%TBSA) burned, affect the outcomes of QoL in burn patients. Additionally, the presence of depression related to post-burn trauma had a significant negative impact on the quality of life. Trauma in any form has a profound impact on the mind of the victim lead to depression and brings about changes in the whole personality of the patient.